Employees with hearing impairment. A qualitative study exploring managers' experiences. Issue 13 (18th June 2020) - Svinndal, Elisabeth Vigrestad; Jensen, Chris; Rise, Marit By
Abstract: Purpose: Explore managers' experiences regarding employees with hearing impairments. Materials and methods: Individual interviews with ten managers having employees with hearing impairment. The interviews were analyzed using Systematic text condensation. Results: The managers felt great responsibility for their employees' functioning, but hearing loss issues were easily forgotten. They found access to information as imperative to secure workplace adjustments, and temporary needs, rather than permanent ones, were easily met. Despite their challenging nature, meetings were not accommodated to meet hearing loss needs. Support in accommodation processes at the workplace was not requested since minor adjustments were perceived as sufficient. Conclusion: The results show that there are barriers towards developing less strenuous working conditions for employees with hearing impairments. The implications of hearing loss should be recognized as risk factors for fatigue and treated accordingly. Appropriate services are necessary to support the stakeholders at the workplace and utilize the room for manoeuver in the accommodation process. Further studies should identify how such services can accommodate both the employees, and managers' needs. IMPLICATIONS FOR REHABILITATION: Hearing loss as a risk factor for fatigue needs to be addressed by rehabilitation professionals. Vocational rehabilitation professionals are needed to support employees with hearing loss and their employers in making adjustments at the work place. Occupational rehabilitation professionals and professionals targeting hearing impairments are both needed in the process.